Differences in Steady-State Erythropoiesis in Different Mouse Bones and Postnatal Spleen - Myneni, Vamsee D.; Szalayova, Ildikó; Mezey, Eva (Frontiers in Cell and Developmental Biology, 2021)
Adult erythropoiesis is a highly controlled sequential differentiation of hematopoietic stem cells (HSCs) to mature red blood cells in the bone marrow (BM). The bones which contain BM are diverse in their structure, embryonic origin, and mode of ossification. This has created substantial heterogeneity in HSCs function in BM of different bones, however, it is not known if this heterogeneity influences erythropoiesis in different bones and different regions of the same bone. In this study, we examined steady state BM erythroid progenitors and precursors from different bones – the femur, tibia, pelvis, sternum, vertebrae, radius, humerus, frontal, parietal bone, and compared all to the femur. Trabecular and cortical regions of the femur were also compared for differences in erythropoiesis. In addition, mouse spleen was studied to determine at which age erythropoietic support by the spleen was lost postnatally. We report that total erythroid cells, and erythroid precursors in the femur are comparable to tibia, pelvis, humerus and sternum, but are significantly reduced in the vertebrae, radius, frontal, and parietal bones. Erythroid progenitors and multipotential progenitor numbers are comparable in all the bones except for reduced number in the parietal bone. In the femur, the epiphysis and metaphysis have significantly reduced number of erythroid precursors and progenitors, multipotential progenitors and myeloid progenitors compared to the diaphysis region. These results show that analysis of erythroid precursors from diaphysis region of the femur is representative of tibia, pelvis, humerus and sternum and have significant implications on the interpretation of the steady-state erythropoiesis finding from adult BM. Postnatal spleen supports erythroid precursors until 6 weeks of age which coincides with reduced number of red pulp macrophages. The residual erythroid progenitor support reaches the adult level by 3 months of age. In conclusion, our findings provide insights to the differences in erythropoiesis between different bones, between trabecular and cortical regions of the femur, and developmental changes in postnatal spleen erythropoiesis.